A review of ultrasound for the diagnosis of acute appendicitis in adults - Pather, Vijay; Gosal, Preet (Journal of Medical Informatics and Decision Making, 2023)
Acute appendicitis is one of the most common surgical emergencies globally, with a lifetime incidence of 8.6% in men and 6.7% in women. While acute appendicitis should be managed promptly to reduce the morbidity associated with perforated appendicitis, morbidity from negative appendicectomy is similar to morbidity from uncomplicated appendicitis. Computer tomography is widely used to aid in the diagnosis of acute appendicitis, however, is costly, often has a slow turn around time, and is associated with exposure to ionising radiation. In contrast, ultrasound is cheap, widely available, requires minimal patient preparation, and does not require exposure to ionising radiation. Ultrasonography is becoming increasingly used for adult patients in emergency settings. The literature has estimated the sensitivity of ultrasound for acute appendicitis in adult patients as between 39-96.4%. The sensitivity and specificity of ultrasound for the diagnosis of acute appendicitis is significantly increased when the appendix is visualised. In cases of a non visualised appendix, indirect ultrasound signs can improve the sensitivity to 93.9% and specificity to 85.7%. The variation in sensitivity and specificity for ultrasound in the diagnosis of acute appendicitis in adults may be due to multiple factors. Ultrasonographer experience, a retrocaecal appendix and obesity have all been described. Given the availability, cost and potential to reduce the rate of negative appendicectomy, ultrasound should be considered as the first line imaging modality for adult patients presenting with suspected AA.
Keywords: Acute Appendicitis; Ultrasound; Diagnosis; Sensitivity; Specificity